OPTIMIZATION ULTRASOUND-ASSISTED EXTRACTION USING CHOLINE CHLORIDE-BASED NATURAL DEEP EUTECTIC SOLVENT TO INCREASE PHENOLIC COMPOUNDS AND ANTIOXIDANTS FROM RHODOMYRTUS TOMENTOSA LEAVES - OKTAVIYANTI, NINA D.; BUDIONO, RYANTO; FITRIANI, ENDANG W.; AVANTI, CHRISTINA (International Journal of Applied Pharmaceutics, 2024)
Objective: The main purpose of this study is to give recommendations for the ideal extraction conditions for improving the extraction yield and antioxidant activity of R. tomentosa leaves. Methods: First, the extraction total phenolic yields of five choline chloride-based Natural Deep Eutectic Solvents (NADES) were evaluated. Then, Box Behnken designs of Response Surface Methodology (RSM) were conducted in order to optimize the extraction condition. The extraction variables investigated were extraction time, water content in NADES, and solid-to-liquid ratio. Meanwhile, total phenolic and 2,2′-azinbis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) free radicals scavenging activity were used as responses. Results: NADES with combination of choline chloride and propylene glycol with a molar ratio of 1:1 was found to be the best solvent for extracting phenolic compound. The total phenolic compound obtained was 29.6351 mg GAE/g dried leaves with ABTS scavenging activity about 96.84% under the optimum extraction condition (extraction time of 60 min, 25% water content in NADES, and solid-to-liquid ratio of 0.02 g/ml). Better results were shown compared to extracts with conventional solvents. Conclusion: In sum, the use of choline chloride-based NADES as extraction solvent under optimum condition was proven to be effective in increasing the extraction efficiency of phenolic compounds and antioxidant activity from R. tomentosa leaves.